Caracterización molecular de las bacterias causantes de otitis externa en caninos - Peñaloza Villalva, Adriana Lisbeth (2025)
In this study, the prevalence in the Guaranda canton was determined using 93 experimental units. The prevalence result was 19.35%, It was classified into four groups: <1 year (5.56%), 1 to 5 years (61.11%), 6 to 10 years (16.67%), and <10 years (16.67%). In terms of breeds, the Poodle was the most affected (27.78%), followed by mixed breeds (27.78%), Shih Tzu (11.11%), French Bulldog (11.11%), Schnauzer (5.56%), Pug (5.56%), German Shepherd (5.56%), and Beagles being the least affected (5.56%). In addition, molecular testing using DNA sequencing identified 33.33% as indeterminate, Acinetobacter (18.52%), Paracoccus (14.81%), Bacillus (11.11%), Sphingomonas (7.41%), Corynebacterium (7.41%), Pseudomonas (3.7%), and Exiguobacterium (3.7%). Otitis is an inflammatory disease and one of the most common conditions affecting general well-being. This research evaluated the antimicrobial activity of Cephalexin, Ciprofloxacin, and Chlorhexidine at concentrations of 5 μg/mL and 10 μg/mL. The most common clinical signs were pruritus and irritation. Finally, secondary pathologies were identified in dogs with otitis, with atopic dermatitis being the most prevalent at 19.35%.